PENDIDIKAN AKHLAK DALAM PERSPEKTIK BUDAYA BATAK TOBA: STUDI PADA MASYARAKAT MUSLIM DI TAPANULI UTARA - Muhammad Abrar Parinduri (LIPI Press, 2020)
This research aimed to investigate the relationship between moral education and local wisdom of the Batak Toba culture. The research used qualitative methods and has been approached with field and ethnography studies. The primary data were obtained from field sources through interviews, observation of social media and supported by any others related documents. While secondary data were obtained from library materials that related to moral education and local wisdom of the Batak Toba culture. This study successfully addressed the implementation of nine Batak Toba local wisdom values which were line to akhlaq education : First, kinship (kekerabatan);Second, religious; Third, hagabeon; Fourth, hasangapon; Fifth, hamoraon; Sixth, hamajuaon; Seventh, patik dohot uhum; Eighth, Pengayoman; Ninth, marsisarian. These values ​​were interrelated with the moral education contents: akhlaq towards Allah, akhlaq towards Rasulullah, akhlaq towards oneself, akhlaq towards family, akhlaq towards community, and akhlaq towards the nation. Moreover, the assimilation between cultural values ​​and moral education were transmitted by parents through family education, family gatherings, and traditional events.